Micromixers and applications - Soon, Chin Fhong; Sundra, Sargunan; Zainal, Nurfarina; Tee, Kian Sek; Ahmad, Mohd Khairul; Wan Omar, Wan Ibtisam; Nayan, Nafarizal (Penerbit Uthm, 2019)
Mixing and dilutions are processes to combine or putting together one or more reagents such as biomolecules, enzyme, proteins and emulsions into the desired concentrations for further applications in chemical and biological applications. The mixing and diluting of chemical solutions in the laboratory require the use of large quantity of plasticwares, consume time and involve with laborious procedures. Micromixing based on microfluidic is a new innovative means to micromix reagents in microliters volume. The reactions of mixing in both active and passive micromixers are dependent on the mass transport phenomena, viscosity of fluid, molecular diffusion and convection. Reynold number indicates if the fluid flow through a channel is steady or turbulent, while Péclet number indicates the magnitude order between convective and diffusive transport. The success of micromixing is also greatly influenced by the velocity, concentration and pressure of fluids. Different methods for fabricating microfluidic device that include etching, thermoforming, polymer ablation, casting and soft-lithography will be reviewed. In addition, the applications of different designs of micromixers in fluid and particles mixing are illustrated in this chapter.